Monatomic catalyst with high specific surface area as well as preparation method and application thereof
By supporting nickel, zinc or zirconium elements on ceria, a single-atom catalyst with a high specific surface area is solved, and the problem of difficulty in activation of CO2 and low methanol conversion is achieved, and the efficient conversion of CO2 and methanol to DMC is achieved.
Patent Information
- Application Number
- CN202411653473.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-18
AI Technical Summary
It is difficult to activate CO2, the methanol conversion rate is low, and the DMC yield of the direct reaction product with methanol is not high.
A single-atom catalyst with a high specific surface area was designed to form a hollow mesoporous structure by supporting nickel, zinc or zirconium elements on ceria, and to regulate the structure and loading of the catalyst to improve the activation of CO2 and methanol and Conversion rate.
The high activity conversion of CO2 and methanol into DMC was achieved, the conversion rate of methanol and the yield of DMC was improved, the constraints of traditional oxide catalysts were broken, and a single-atom catalyst was developed for direct generation of DMC with CO2 and methanol.
Smart Images

Figure CN119455963A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chemical catalysis, and in particular to a single-atom catalyst. Background Art
[0002] As an environmentally friendly chemical reagent, DMC is widely used in organic synthesis, lithium battery electrolyte, coating, polycarbonate synthesis and medicine due to its safety and low toxicity. Its demand is increasing year by year and it has received more and more attention in the modern chemical industry. The earliest method for industrial production of DMC was the phosgene method, which is now being gradually eliminated by the market due to the use of highly toxic phosgene and the production of toxic byproduct hydrochloric acid. The raw materials used in the methanol oxidative carbonylation method are not only toxic, but also have a high risk of explosion when mixed with oxygen, posing a great safety hazard to production work. Although the ester exchange method can obtain DMC with a high yield, the atomic utilization rate is low, and its byproduct selectivity is also very high, resulting in high separation costs. In addition, the byproduct NH3 produced by the urea alcoholysis method will adhere to the active site of the catalyst, resulting in catalyst deactivation. In recent years, with the continuous development and optimization of DMC synthesis methods, the emerging route of direct synthesis of DMC from CO2 and methanol has gradually come to the stage. This reaction route has mild conditions, does not use hydrogen, has high atomic utilization, and produces environmentally friendly by-products that are easy to separate. It can not only improve the selectivity of DMC and reduce the cost of CO2 resource utilization, but also help reduce dependence on traditional petroleum-based raw materials, which is in line with the concept of sustainable economic development and green energy chemistry.
[0003] At present, researchers have analyzed the reaction mechanism of DMC synthesis from CO2 and methanol and found that the adsorption and activation of CO2 are the rate-determining steps of the reaction kinetics. Therefore, researchers have been committed to designing catalyst systems with higher catalytic activity for CO2. Researchers have carried out a lot of research work in improving preparation methods, adding additives and modifying catalyst structures. From the structure-activity relationship study of catalyst structural properties and catalytic performance, it was found that oxygen vacancies and acid-base sites may be the key active centers for CO2 activation and dissociation. Nanocatalysts are precisely modified and modified at the microscopic scale, and the composition and surface structure of the catalyst are adjusted to obtain more active centers to promote DMC synthesis. Therefore, modifying metal oxides with abundant oxygen vacancies and acid-base sites for efficient activation of CO2 has become the mainstream research direction of this reaction.
[0004] With the further understanding of the mechanism of catalytic reactions and the structure-activity relationship between catalysts and performance, the factors affecting catalytic activity are no longer limited to the activation of inert CO2 molecules, but focus on the rapid conversion of intermediates. Xie Yi's team systematically constructed surface vacancy cluster-mediated solid hindered Lewis acid-base pairs (FLPs) using cerium oxide as a model, achieving efficient conversion of methanol to DMC. Synchrotron radiation and in situ characterization combined with theoretical calculations showed that the FLPs sites on the surface of cerium oxide can effectively accelerate the formation and conversion of key reaction intermediates (CH3OCOO*), thereby promoting the formation of DMC.
[0005] However, whether it is for CO2 activation and dissociation or accelerating the conversion of key reaction intermediates, the methanol conversion rate in all catalytic systems is still very low. At present, the main problem of the unsatisfactory yield of DMC synthesis from CO2 and methanol is the difficulty in CO2 activation and the low methanol conversion rate. CO2 contains lone electron pairs and is stable in nature. It is difficult to be adsorbed and activated by the catalyst during the reaction. Therefore, the activation of CO2 is a key factor affecting the reaction rate. The selection of appropriate catalysts with unique structures plays a decisive role in the reaction. In recent years, the development of single-atom catalysts has greatly promoted the development of the catalytic field, but the current research on catalysts still revolves around the generation of abundant oxygen vacancies (O V ) to promote the catalytic oxidation process of CO2 to improve catalytic activity, and single-atom catalysts have not been studied before. Single-atom catalysts refer to isolated metal atoms supported on the surface of a carrier as active sites, which have attracted widespread attention due to their unique catalytic effect and sufficient atomic efficiency.
[0006] At present, the main problem of the unsatisfactory yield of DMC synthesized from CO2 and methanol is the difficulty in CO2 activation and the low methanol conversion rate. In recent years, the metal oxide catalysts used in the reaction have not broken the methanol conversion rate of 1.0%. Therefore, in order to improve the methanol conversion rate and DMC yield in the preparation of DMC from CO2 and methanol, it is necessary to develop a highly active catalyst with a unique structure. Summary of the invention
[0007] In view of the problems that CO2 is difficult to activate, the methanol conversion rate is low and the yield of DMC, the product of the direct reaction with methanol, is not high, the present invention provides a single-atom catalyst with a high specific surface area, a preparation method and its application, designs a hollow mesoporous catalyst with a high specific surface area, further loads transition metal nickel, and regulates the ability of the cerium dioxide carrier to adsorb and activate CO2, thereby improving the activity of the catalyst in the direct production of DMC by CO2 and methanol and the yield of the product.
[0008] The object of the present invention is achieved in this way: a single-atom catalyst with a high specific surface area comprises cerium dioxide, nickel, zinc and zirconium, wherein the nickel, zinc and zirconium elements are loaded on the cerium dioxide.
[0009] Furthermore, the mass of the metal elements in the nickel, zinc and zirconium elements is 0.07% to 2.7% of the total mass of the metals in the catalyst.
[0010] A method for preparing a single-atom catalyst with a high specific surface area comprises the following steps:
[0011] Step (1): a solution containing cerium element reacts with a precipitant to obtain a precursor, and then drying to obtain a composite;
[0012] Step (2): Mixing a solution containing nickel, zinc or zirconium elements with the complex to prepare a single atom catalyst.
[0013] Furthermore, the cerium-containing solution in step (1) is selected from at least one of cerium nitrate and cerium chloride; the precipitant is selected from one of urea and sodium hydroxide; and the concentration of the urea or sodium hydroxide is 0.25-14 mol / L.
[0014] Furthermore, the solution containing nickel, zinc or zirconium in step (2) is selected from one of nitrate and chloride; the mass of the metal element loaded on the catalyst accounts for 0.07% to 2.7% of the total mass of the metal in the catalyst.
[0015] Furthermore, the precursor in step (1) includes a solvent and a precipitant;
[0016] The solvent is deionized water;
[0017] The volume of the deionized water is 8-70 mL;
[0018] The precipitant is urea or sodium hydroxide;
[0019] The concentration of urea or sodium hydroxide is 0.25~14 mol / L;
[0020] In step (2), before the mixing, the process of pre-treating the composite is also included, and the pre-treatment is drying or drying and calcining; after the mixing, the process of post-treatment is also included, and the post-treatment process includes stirring, drying, calcining or stirring, drying, calcining and reducing in sequence.
[0021] Furthermore, in step (1), the stirring temperature is 20-100°C; the stirring time is 0.5-12 h; the Ph value of the precursor solution is 3-12; sodium hydroxide is selected as the precipitant, the hydrothermal temperature is 60-180°C, and the hydrothermal time is 5-36 h; urea is selected as the precipitant, the hydrothermal temperature is 100-220°C, and the hydrothermal time is 5-24 h; the drying temperature is 60-100°C, and the drying time is 5-12 h;
[0022] Furthermore, in step (2), the pretreatment conditions are as follows: drying temperature is 60-100 °C, drying time is 5-12 h; calcination temperature is 400-800 °C; calcination time is 2-6 h; calcination is carried out under inert atmosphere; the inert atmosphere is selected as air atmosphere; in the post-treatment process, the stirring temperature is 20-100 °C; stirring time is 0.5-12 h; calcination temperature is 400-800 °C; calcination time is 2-6 h; calcination is carried out under inert atmosphere; calcination and reduction are carried out under inert atmosphere; reduction is carried out under hydrogen atmosphere; reduction temperature is 200-600 °C; reduction time is 1-3 h.
[0023] A method for directly preparing DMC from CO2 and methanol comprises mixing a single atom catalyst with a reactant, methanol, and stirring the mixture in a reactor containing CO2 gas to react and prepare DMC.
[0024] Furthermore, the single atom catalyst is placed in a reactor, methanol as a reactant is added, CO2 is introduced, and after the air inside the reactor is replaced, CO2 gas is filled into the reactor to reach the reaction pressure; a contact reaction occurs to prepare DMC; the mass of the single atom catalyst is 0.1-0.2 g, the volume of the solvent methanol is 5-25 mL; the initial pressure of CO2 is 0-10 MPa; the reaction temperature is 130-150 °C; and the reaction time is 4-6 h.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] (1) Due to its special electronic structure, ceria has properties similar to precious metals. The prepared ceria with a hollow mesoporous structure with a high specific surface area can be used as a carrier to effectively and quickly transport and adsorb and activate CO2 and methanol. By introducing the second active component nickel, which can efficiently activate CO2 to carbonyl species, into the ceria catalyst that can convert CO2 and methanol into DMC, the nickel element is loaded on the ceria. By adjusting the loading amount and chemical state of the metal nickel, a composite catalyst with dual active centers is formed, so that the catalyst has excellent catalytic activity in the reaction of converting CO2 and methanol into DMC, achieving high activity of CO2 and methanol to DMC while having a high methanol conversion rate.
[0027] (2) This catalyst breaks the shackles of traditional oxide catalysts and develops a single-atom catalyst for direct generation of DMC from CO2 and methanol. The prepared single-atom catalyst has large straight cylindrical pores and a large specific surface area. At the same time, the nickel loading allows the catalyst to produce more oxygen vacancies and form abundant Lewis acid-base sites. It is a single-atom catalyst with a mesoporous structure.
[0028] (3) The catalyst has a simple preparation method, high catalytic efficiency, strong operability, and is easy to control, with broad development space and market application. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0030] Figure 1 TEM image of the 1% Ni / CeO2(H2) catalyst prepared in Example 1 of the present invention
[0031] Figure 2 XPS graph of the 1% Ni / CeO2(H2) catalyst prepared in Example 1 of the present invention DETAILED DESCRIPTION
[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0034] In the examples of the present application, the catalyst evaluation, conversion rate and product yield calculation methods are as follows:
[0035] The activity evaluation of the catalyst in the reaction of CO2 and methanol to produce DMC is carried out in a high-pressure closed reactor. The specific experimental process is as follows:
[0036] A microreactor (100 mL) equipped with an electric heater and a magnetic stirrer was used to test the performance of the catalyst in the transesterification reaction. Reaction conditions: CO2 initial pressure 3.0 MPa, methanol volume 20 mL, 0.1~0.2 g of catalyst was added, heated to 130~150℃ and reacted for 4~6 h under continuous stirring.
[0037] The content of the product was measured using the internal standard method (n-butanol as the internal standard). First, the standard sample was injected into a gas chromatograph equipped with a flame ionization detector (FID). The n-butanol and methanol used in the standard sample were chromatographic grade (n-butanol as the internal standard), and the correction factors of the raw material (methanol) and the product (DMC) were obtained. After the catalytic reaction was completed, the reactor was placed in an ice-water bath and cooled to a low temperature. Then, the pressure was released and the kettle was opened. A certain amount of n-butanol was added. After stirring evenly, part of the reaction liquid was taken out and the catalyst was recovered. The reactants were quantified using a gas chromatograph (HF-900) equipped with an FID detector and a FFAP capillary column (60 m×0.25 mm). The column chamber temperature, vaporization chamber temperature and hydrogen flame temperature were 220 ℃, 260 ℃ and 280 ℃, respectively. The initial column temperature was 60 ℃, maintained for 3 min, and then heated to 210 ℃ at a rate of 10 ℃ / min and maintained for 1 min. Equal amounts of reaction liquid were added to the same gas chromatograph, and the amount of raw materials and by-products was obtained by internal standard method. The main product was DMC. Methanol conversion rate (X CH3OH ), DMC yield (Y DMC ) is calculated according to the following formula:
[0038] X CH3OH = (Formula 1)
[0039] Y DMC = × 1000 (mmol.g -1 ) (Formula 2)
[0040] Among them, n CH3OH,feed is the initial molar amount of methanol, n CH3OH,detected is the remaining molar amount of methanol after the reaction, n DMC,detected Y is the molar amount of DMC generated after the reaction.DMC is the DMC yield.
[0041] Example 1
[0042] A method for preparing a single-atom catalyst with a high specific surface area comprises the following steps:
[0043] Step (1) Weigh 3.0 g of Ce(NO3)3·6H2O and add it to 8 mL of deionized water, add urea, the urea concentration is 0.25 mol / L, and stir for 1 h at 25°C. After the reaction is completed, the generated white solid is washed with 200 mL of deionized water until the Ph is 7, filtered, and dried at 80°C for 10 h to obtain a composite;
[0044] Step (2) Dissolve 2 g of the above complex completely in 10 mL of deionized water. Ni / m (Ce+Ni) The above-mentioned composite was added with 1% corresponding mass Ni(NO3)2·6H2O, stirred at 25°C for 12 h, and dried at 80°C for 10 h; the dried solid was further placed in a tubular furnace for calcination and reduction, and was heated to 600°C at 2°C / min in an air atmosphere and calcined for 4 h; after cooling to room temperature, it was heated to 400°C at 2°C / min in a hydrogen atmosphere and reduced for 2 h to finally obtain a single atom catalyst sample.
[0045] The reaction conditions are 140 °C, 3 MPa, 20 mL methanol, and 5 h, which is used in the reaction of CO2 and methanol to produce DMC.
[0046] Example 2
[0047] The method is the same as in Example 1, except that the nickel loading in step (2) is changed to add m Ni / m (Ce+Ni) The corresponding mass is 0.07% Ni(NO3)2·6H2O.
[0048] The evaluation results of the reaction are shown in Table 1. The remaining specific steps and reaction conditions are the same as those in Example 1.
[0049] Example 3
[0050] The method is the same as in Example 1, except that the nickel loading in step (2) is changed to add m Ni / m (Ce+Ni) The corresponding mass is 2.7% Ni(NO3)2·6H2O.
[0051] The evaluation results of the reaction are shown in Appendix 1, and the remaining specific steps and reaction conditions are the same as in Example 1.
[0052] Example 4
[0053] The method is the same as in Example 1. 3.0 g of Ce(NO3)3·6H2O is weighed and added into 70 mL of deionized water with a sodium hydroxide concentration of 14 mol / L. Ni / m (Ce+Ni) The corresponding mass of Ni(NO3)2·6H2O was 0.07%, the hydrothermal temperature was changed to 100 ℃, the hydrothermal time was 24 h, and after cooling, it was filtered and washed with deionized water until the pH was 7.
[0054] The evaluation results of the reaction are shown in Table 1. The remaining specific steps and reaction conditions are the same as those in Example 1.
[0055] Example 5
[0056] The method was the same as in Example 1. 3.0 g of Ce(NO3)3·6H2O was weighed and added into 70 mL of deionized water. The concentration of sodium hydroxide was 14 mol / L. The hydrothermal temperature was changed to 100 °C and the hydrothermal time was 24 h. After cooling, the mixture was filtered and washed with deionized water until the pH was 7.
[0057] The evaluation results of the reaction are shown in Table 1. The remaining specific steps and reaction conditions are the same as those in Example 1.
[0058] Example 6
[0059] The method is the same as that of Example 1, except that the nickel nitrate hexahydrate in step (2) is replaced with zinc nitrate hexahydrate, and m Ni / m (Ce+Zn) The corresponding mass is 1% Zn(NO3)2·6H2O.
[0060] The evaluation results of the reaction are shown in Table 1. The remaining specific steps and reaction conditions are the same as those in Example 1.
[0061] Example 7
[0062] The method is the same as in Example 1, except that the nickel nitrate hexahydrate in step (2) is replaced by zirconium nitrate pentahydrate, and m Ni / m (Ce+Zr) The corresponding mass of Zr(NO3)4 is 1% . 5H2O.
[0063] The evaluation results of the reaction are shown in Table 1. The remaining specific steps and reaction conditions are the same as those in Example 1.
[0064] Example 8
[0065] The reaction conditions in Example 1 were changed and the reaction time was changed to 4 h.
[0066] The evaluation results of the reaction are shown in Table 1. The remaining specific steps and reaction conditions are the same as those in Example 1.
[0067] Example 9
[0068] The reaction conditions in Example 1 were changed and the reaction time was changed to 6 h.
[0069] The evaluation results of the reaction are shown in Appendix 1, and the remaining specific steps and reaction conditions are the same as in Example 1.
[0070] Example 10
[0071] The reaction conditions in Example 1 were changed by changing the reaction temperature to 130°C.
[0072] The evaluation results of the reaction are shown in Appendix 1, and the remaining specific steps and reaction conditions are the same as in Example 1.
[0073] Embodiment 11
[0074] The reaction conditions in Example 1 were changed by changing the reaction temperature to 150°C.
[0075] The evaluation results of the reaction are shown in Appendix 1, and the remaining specific steps and reaction conditions are the same as in Example 1.
[0076] Example 12
[0077] Step (2) in Example 1 was changed to place the dried solid in a tube furnace for calcination. The temperature was increased to 600° C. at a rate of 2° C. / min under a nitrogen atmosphere and calcined for 4 h.
[0078] The evaluation results of the reaction are shown in Appendix 1, and the remaining specific steps and reaction conditions are the same as in Example 1.
[0079] Embodiment 13
[0080] The method is the same as in Example 1, except that the nickel loading in step (2) is changed to add m Ni / m (Ce+Ni) The corresponding mass of Ni(NO3)2·6H2O is 0.07%; step (2) in Example 1 is changed, and the dried solid is further placed in a tubular furnace for calcination. In a nitrogen atmosphere, the temperature is increased to 600°C at 2°C / min and calcined for 4 hours.
[0081] The evaluation results of the reaction are shown in Appendix 1, and the remaining specific steps and reaction conditions are the same as in Example 1.
[0082] Embodiment 14
[0083] The method is the same as in Example 1, except that the nickel loading in step (2) is changed to add m Ni / m (Ce+Ni)The corresponding mass of Ni(NO3)2·6H2O is 2.7%; step (2) in Example 1 is changed, and the dried solid is further placed in a tube furnace for calcination and reduction. After calcination, the temperature is increased to 600°C at 2°C / min under a nitrogen atmosphere and calcined for 4 hours.
[0084] The evaluation results of the reaction are shown in Appendix 1, and the remaining specific steps and reaction conditions are the same as in Example 1.
[0085] Embodiment 15
[0086] The method is the same as that of Example 1. The composite obtained in step (1) is subjected to the pretreatment of step (2) and calcined in air for 2 h at a calcination temperature of 400° C. The subsequent steps remain unchanged.
[0087] The evaluation results of the reaction are shown in Appendix 1, and the remaining specific steps and reaction conditions are the same as in Example 1.
[0088] Table 1 Effects of different catalysts and conditions on the performance of DMC catalysts for the production of CO2 and methanol
[0089] As shown in Examples 1 to 15 in Table 1, according to the experimental results, compared with Example 1, Examples 2-14 show relatively low performance. It is shown that the preferred catalyst is 1% Ni / CeO2(H2), the preferred reaction temperature is 140°C, and the reaction time is 5 h, indicating that the appropriate amount of loaded metal, reaction temperature and reaction time have a great influence on the performance of the catalyst. When the reaction time is less than 5 h, the reaction is not completely carried out, the activation conversion of CO2 and methanol is inhibited, the reaction efficiency is weakened, and the activity is reduced; if the reaction time is too long, the catalyst activity is reduced and the product yield is reduced because the reaction is a reversible reaction and there is the generation of byproduct water; the reaction temperature is too low or too high, which reduces the catalyst's ability to activate CO2, and also affects the carbon-carbon coupling process, resulting in a reduction in the conversion rate of methanol. Compared with other metals, nickel loading promotes the formation of Ov, and single-atom dispersed nickel has excellent performance in CO2 activation; compared with nanorod catalysts formed with sodium hydroxide as a precipitant, the 1%Ni / CeO2(H2) catalyst with hollow channels can not only improve the CO2 transmission capacity, but also expose more active sites due to its high specific surface area. It can be seen that the 1%Ni / CeO2(H2) catalyst achieves 100% utilization of metal atoms, and the special morphology finally presents makes the catalyst expose more advantageous crystal faces and a large specific surface area, and the confinement effect of its own mesoporous structure and the synergy between the dual-functional characteristics brought by the sufficient oxygen defect sites to promote CO2 activation and the CO2 adsorption activation mechanism greatly improve the conversion rate of methanol and the yield of DMC.
[0090] In the process of directly preparing DMC from CO2 and methanol, the adsorption activation of CO2 and methanol is a prerequisite for the reaction to occur. CO2, as a non-polar molecule, is highly inert and difficult to activate. Due to its special electron-bearing structure, cerium dioxide has abundant oxygen vacancies and oxygen migration, thereby having a strong activation ability for both CO2 and methanol. The object of the present invention is to provide a catalyst for directly preparing DMC from CO2 and methanol with high activity, especially high methanol conversion rate, according to the characteristics of the reaction of CO2 and methanol.
[0091] A large number of studies have shown that cerium dioxide has the properties of both Lewis acid and Lewis base, and is a basic oxide with abundant oxygen vacancies and oxygen migration. By regulating the morphology, structure, content and chemical state of the loaded metal of cerium dioxide, abundant oxygen vacancies and Lewis acid-base pairs can be obtained to a certain extent, and this property makes it widely used in the field of DMC synthesis. Nickel-based catalysts are inexpensive and have catalytic activity similar to that of precious metal-based catalysts, and isolated nickel has excellent activity for the conversion of CO2 into carbonyl species, and is also widely used in the field of catalysis. The catalyst prepared by the present invention is 1% Ni / CeO2(H2), which is a single-atom catalyst with a unique structure.
[0092] The loading of transition metal nickel enables the cerium-based catalyst to obtain efficient catalytic activity and stability, which comes from the unique structure of the catalyst. The single-atom catalyst with straight hollow channels can not only improve the transmission capacity of CO2, but also achieve 100% utilization of metal atoms. The special morphology finally presents more advantageous crystal faces and large specific surface area of the catalyst. More OVs produced by the metal loading can act as Lewis acid and alkaline sites in chemical properties, which may greatly reduce the reaction energy barrier. Especially after hydrogen reduction, the confinement effect of its own mesoporous structure and the synergy between the dual functional characteristics brought by the sufficient oxygen defect sites to promote CO2 activation and the CO2 adsorption activation mechanism greatly improve the conversion rate of methanol and the yield of DMC.
[0093] The 1% Ni / CeO2(H2) prepared by the present invention uses hollow mesoporous cerium dioxide with a high specific surface area as a carrier, which can effectively activate CO2 and methanol. The hollow mesoporous structure is conducive to the rapid transmission of CO2, and the isolated nickel atoms have the ability to dissociate and adsorb CO2 to form carbonyl species. This catalyst has the advantages of high activity, high specific surface area and hollow mesopores in the reaction of CO2 and methanol, and is a single atom catalyst with great application prospects.
[0094] The above embodiments are only used to help understand the method and core idea of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A single-atom catalyst with a high specific surface area, characterized in that: The invention comprises cerium dioxide, nickel, zinc and zirconium, wherein the nickel, zinc and zirconium elements are loaded in the cerium dioxide.
2. The single-atom catalyst with a high specific surface area according to claim 1, characterized in that The mass of the metal elements in the nickel, zinc and zirconium elements is 0.07% to 2.7% of the total mass of the metals in the catalyst.
3. A method for preparing a single-atom catalyst having a high specific surface area as claimed in claim 1 or 2, characterized in that: The following steps are involved: Step (1): a solution containing cerium element reacts with a precipitant to obtain a precursor, and then drying to obtain a composite; Step (2): Mixing a solution containing nickel, zinc or zirconium elements with the complex to prepare a single atom catalyst.
4. The preparation method according to claim 3, characterized in that: The cerium-containing solution in step (1) is selected from at least one of cerium nitrate and cerium chloride; the precipitant is selected from one of urea and sodium hydroxide; and the concentration of the urea or sodium hydroxide is 0.25-14 mol / L.
5. The preparation method according to claim 4, characterized in that: The solution containing nickel, zinc or zirconium in step (2) is selected from one of nitrate and chloride; the mass of the metal element loaded on the catalyst accounts for 0.07% to 2.7% of the total mass of the metal in the catalyst.
6. The preparation method according to claim 5, characterized in that: The precursor in step (1) includes a solvent and a precipitant; The solvent is deionized water; The volume of the deionized water is 8-70 mL; The precipitant is urea or sodium hydroxide; The concentration of urea or sodium hydroxide is 0.25~14 mol / L; In step (2), before the mixing, the process of pre-treating the composite is also included, and the pre-treatment is stirring, drying or stirring, drying and calcining; after the mixing, the process of post-treatment is also included, and the post-treatment process includes stirring, drying, calcining or stirring, drying, calcining and reducing in sequence.
7. The preparation method according to claim 6, characterized in that: In step (1), the stirring temperature is 20-100°C; the stirring time is 0.5-12 h; the Ph value of the precursor solution is 3-12; sodium hydroxide is selected as the precipitant, the hydrothermal temperature is 60-180°C, and the hydrothermal time is 5-36 h; urea is selected as the precipitant, the hydrothermal temperature is 100-220°C, and the hydrothermal time is 5-24 h; the drying temperature is 60-100°C, and the drying time is 5-12 h.
8. The preparation method according to claim 7, characterized in that: In step (2), the pretreatment conditions are as follows: drying temperature of 60-100 °C, drying time of 5-12 h; calcination temperature of 400-800 °C; calcination time of 2-6 h; calcination is carried out under inert atmosphere; the inert atmosphere is selected as air atmosphere; in the post-treatment process, the stirring temperature is 20-100 °C; stirring time of 0.5-12 h; calcination temperature of 400-800 °C; calcination time of 2-6 h; calcination is carried out under inert atmosphere; calcination and reduction are carried out under inert atmosphere; reduction is carried out under hydrogen atmosphere; reduction temperature is 200-600 °C; reduction time is 1-3 h.
9. A method for directly preparing DMC from CO2 and methanol, characterized in that: The single atom catalyst according to claim 1 to 2 or the single atom catalyst prepared by the method according to any one of claims 3 to 8 is mixed with the reactant methanol, and stirred in a reactor containing CO2 gas to react to prepare DMC.
10. The method for directly preparing DMC from CO2 and methanol according to claim 9, characterized in that: The single atom catalyst is placed in a reactor, reactant methanol is added, CO2 is introduced, and after the air inside the reactor is replaced, CO2 gas is filled into the reactor to reach the reaction pressure; a contact reaction occurs to prepare DMC; the mass of the single atom catalyst is 0.1~0.2 g, the volume of the solvent methanol is 5~25 mL; the initial pressure of CO2 is 0~10 MPa; the reaction temperature is 130~150°C; and the reaction time is 4~6 h.